Três décadas de tentativas de estabilização da economia brasileira - Leme, Thomaz de Aquino Garcez (1993)
The present study, which was elaborated in order to fulfil the last necessary requirement to obtain the title of Doctor in Business Affairs, through the Escola de Administração de Empresas de São Paulo da Fundação Getúlio Vargas, has the purpose of studying the efficiency of the different adjustment programs applied to the Brazilian economy in the last three decades. In the first chapter it was studied the behaviour of the Brazilian economy from the beginning of the sixties. At that time it was verified, simultaneously, an accelerated increase in the industrial area as well as a slowly but persistent increment of the inflation rate. After an institutional rupture in the middle of that decade, the new economical policy adopted had a strict orthodox characteristic, that would lead the country to live a period of high growth rates, after a time of recession. In the second chapter it was analysed the seventies. In the beginning of that decade high product increment rates took place resulting from a good performance of the industrial field, which was impaired in 1973 by the first shock in the prices of Gil and worsened by the second Gil price raise in 1979, linked to an expressive elevation of the international interest rates. These last facts changed thoroughly the profile of our economy. In the third and last chapter the economy in the eighties was looked into. The first half of that decade was particularly different because of the difficulties caused by the energy shocks due to the Gil crisis, associated with the aggravation of the external debt. Attempting to revert the bad situation, several economical experiments with heterodox features were put into practice such as Plano Cruzado, the first of them, and more recently the unsuccessful Plano Collor, launched in the first months of 1990. It was verified that none of the adjustment attempts were successful, as the attained results were not the expected ones. But, in some aspects, it must be considered the occurrence of healthy transformations, which were necessary to a better performance of the economy.